Smart Home Automation System - Azizul, Dhia Nadhirah; Abd Kamal, Farahizzatul Najwa; Omar, Mastura (2020)
Smart Home Automation System is a project to develop a prototype of home automation system using an-Arduino MEGA 2560 microcontroller. This project include the automatic opening and closing door system, automatic light control system and automatic fan controlled system based on temperature of the room. The door will be using Ultrasonic sensor and rotational moving motor connected to gear which will drive rail to slide the door open and close. Then, the lights will automatically turn on when someone enter the house (within the range of the house area). After that, the automatic fan control is based on the temperature of the room. As technology is advancing so houses are also getting smarter. Usually, conventional switches located in different parts of the house makes it difficult for elderly or physically handicapped people to do so. This home automation system is providing a solution to these problems. Therefore, this home automation system should be required by elderly and physically handicapped people as it is important to consider issue of controlling , monitoring electrical appliances and energy management in their houses.